Steel Structural and Functional Characteristics Focusing on Corrosion Mechanisms - Rajesh Kumar Singh; Vikas Kumar; Yashwant Ray Balwant (International Journal of Minerals, 2025)
This research article examines steel structural and functional characteristics, focusing on corrosion mechanisms and inhibitor protection strategies. Steel corrosion affects numerous industries, causing significant economic losses and safety risks. Fundamental electrochemical processes behind various corrosion forms including uniform, pitting, crevice, galvanic, intergranular, and stress-induced corrosion are explained. The chapter highlights the steel industry's importance while investigating how corrosion impacts performance and longevity. Protection methods discussed include material selection, environmental modification, sacrificial anodic, impressed current and organic inhibitors. Special attention is given to corrosion inhibitor and their classification, action mechanisms, and design parameters. Inhibitor adsorption and precipitation behaviours are analyzed along with chemical compatibility requirements. The text covers raw materials, synthesis pathways, formulation strategies, and monitoring techniques for effective inhibitor implementation. Raw materials including fatty acids, amines, and their derivatives are detailed alongside formulation considerations such as solubility and stability. Testing methodologies for evaluating inhibitor performance under various conditions are presented, from static tests to dynamic flow simulations. This comprehensive information provides valuable insights for researchers and industry professionals seeking sustainable, cost-effective corrosion protection solutions for steel.
Keywords: Corrosion protection; Steel corrosion; adsorption behaviour; corrosion inhibitors; corrosion mechanisms; electrochemical processes; steel durability